2008
DOI: 10.1063/1.3050522
|View full text |Cite
|
Sign up to set email alerts
|

Study on characteristics of thermally stable HfLaON gate dielectric with TaN metal gate

Abstract: We have fabricated the thinnest equivalent oxide thickness of 0.62 nm HfLaON gate dielectric for TaN/HfLaON/SiOx gate stack with improved thermal stability and electrical characteristics. The HfLaON film was deposited using reactive sputtering of Hf–La and Hf targets by alternate means in N2/Ar ambience. The effects of different postdeposition annealing conditions and various La contents on the properties of HfLaON film and its interface have been investigated; the corresponding mechanisms are discussed. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…This observation is in accordance with the deposition sequence, and contributes to a good HfLaON/SiO 2 interface, because Hf is chemically more stable than La when contacting with SiO 2 [5]- [7]. The atomic ratio of La/(La+Hf) in the HfLaON composite film is calculated to be 46 % from the EDS analysis, and this high La content is helpful to keep the HfLaON film amorphous even at a high annealing temperature up to 1000 o C [8]. sample displays higher P/E speeds and larger memory window than the LaON one under the same operating conditions.…”
Section: Results and Disscusionsupporting
confidence: 72%
See 1 more Smart Citation
“…This observation is in accordance with the deposition sequence, and contributes to a good HfLaON/SiO 2 interface, because Hf is chemically more stable than La when contacting with SiO 2 [5]- [7]. The atomic ratio of La/(La+Hf) in the HfLaON composite film is calculated to be 46 % from the EDS analysis, and this high La content is helpful to keep the HfLaON film amorphous even at a high annealing temperature up to 1000 o C [8]. sample displays higher P/E speeds and larger memory window than the LaON one under the same operating conditions.…”
Section: Results and Disscusionsupporting
confidence: 72%
“…On the other hand, HfON, which shows a smaller dielectric constant (~ 22) than La 2 O 3 (~ 30) [3], [6], is wellknown for its thermodynamic stability with SiO 2 ; consequently, a good interface can be expected between HfON and SiO 2 [6]. Both La 2 O 3 and HfON films present poor thermal stability with a low crystallization temperature; on the contrary, it is widely reported that the HfLaON composite film displays better thermal stability with a higher crystallization temperature than the HfON or La 2 O 3 film [8]. Therefore, based on MONOS capacitors, this work aims to study the charge-trapping characteristics of HfLaON by comparing with nitrided La 2 O 3 .…”
Section: Introductionmentioning
confidence: 96%
“…Currently, nitrided La doped HfO 2 dielectric exhibits the amorphous structure after 1000°C rapid thermal annealing and has a large conduction band offset, which lowers the leakage current. Xu et al have investigated the characteristics of TaN/ HfLaON/SiO x gate stack MOS capacitors with the thinnest EOT of HfLaON gate dielectric down to 0.62 nm [157]. When the ratio of La/Hf + La isnot less than 35%, the thin film remains amorphous at a high temperature up to 1000°C (Fig.…”
Section: Hf-based Oxides Gate Dielectricsmentioning
confidence: 97%
“…Besides HfSiON and HfAlON, HfO 2 film was also alloyed with some other elements, such as Ti, Ta, or La to form HfO 2 -based gate dielectrics [155][156][157][158]. Addition of Ti in Hf oxide can form Hf/Ti-based oxide or oxynitride with higher k value because Ti oxide has higher k value than Hf oxide.…”
Section: Hf-based Oxides Gate Dielectricsmentioning
confidence: 99%
“…This was indicative of reduced oxygen vacancy concentration. Xu [37] reported the fabrication of HfLaON gate dielectrics with an EOT of 0.62 nm to suppress tunneling leakage. La doping was demonstrated to enhance the k value of the dielectrics and Alshareef et al [23] observed that the addition of Al into Hf-based high-k materials could passivate the oxygen vacancy 0 V  which induced midgap states but there was with little influence by other aspects of the defects .…”
Section: Dual-dipole Formation In Mos Stackmentioning
confidence: 99%